2022
DOI: 10.3390/biomedicines10123083
|View full text |Cite
|
Sign up to set email alerts
|

Monocytic Cell Adhesion to Oxidised Ligands: Relevance to Cardiovascular Disease

Abstract: Atherosclerosis, the major cause of vascular disease, is an inflammatory process driven by entry of blood monocytes into the arterial wall. LDL normally enters the wall, and stimulates monocyte adhesion by forming oxidation products such as oxidised phospholipids (oxPLs) and malondialdehyde. Adhesion molecules that bind monocytes to the wall permit traffic of these cells. CD14 is a monocyte surface receptor, a cofactor with TLR4 forming a complex that binds oxidised phospholipids and induces inflammatory chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 91 publications
(102 reference statements)
0
1
0
Order By: Relevance
“…The adhesion of monocytes to the vascular endothelium is important in the initiation and progression of atherosclerosis [27]. OxLDL markedly increased the adhesion of monocytes to HUVEC monolayers and this was decreased by either olaparib or MCC950 (Fig 6A).…”
Section: Parp Inhibition By Olaparib Attenuated Oxldl-induced Monocyt...mentioning
confidence: 97%
“…The adhesion of monocytes to the vascular endothelium is important in the initiation and progression of atherosclerosis [27]. OxLDL markedly increased the adhesion of monocytes to HUVEC monolayers and this was decreased by either olaparib or MCC950 (Fig 6A).…”
Section: Parp Inhibition By Olaparib Attenuated Oxldl-induced Monocyt...mentioning
confidence: 97%
“…Importantly, the interaction between MDA and proteins or amino acids yields unstable carboxylation products known as advanced glycation end products, which induce oxidation and structural damage to cell membrane lipids, and negatively affect the normal functioning of the microvasculature [41]. Furthermore, studies have indicated that MDA promotes platelet aggregation, as well as the synthesis and release of thromboxane A2, and consequently stimulates platelet activation and thrombosis [42,43]. Promising prospects include inhibiting malondialdehyde production and metabolism to enhance microvascular function and alleviate complications in people with diabetes.…”
Section: Mdamentioning
confidence: 99%
“…Since thrombolytic therapy is limited by many factors and angiography is required to determine the extent of IRA reperfusion [6], PPCI treatment as soon as possible is the most effective reperfusion method for STEMI patients [7][8][9]. Guidelines recommend that STEMI patients start anticoagulation therapy before PPCI, which can effectively block the coagulation cascade, reduce thrombosis, inhibit the further development of thrombosis, and even promote the dissolution of coronary thrombosis and the re-opening of IRA [10]. Yet the start timing for a PPCI preoperative anticoagulant ther-apy study is less, and there is no clear early heparin anticoagulationization large clinical study of IRA recanalization.…”
Section: Introductionmentioning
confidence: 99%